2021
DOI: 10.1186/s43055-021-00474-5
|View full text |Cite
|
Sign up to set email alerts
|

Conventional ultrasound, color Doppler, TI-RADS, and shear wave elastography for thyroid nodule differentiation: a study of efficacy compared with the histopathology results

Abstract: Background Although a minority of the thyroid nodules is malignant, usually the invasive diagnostic procedures are warranted. This prospective study aims to assess the diagnostic performance of the US criteria in addition to the TI-RADS score and the SWE for the differentiation between the benign and malignant thyroid nodules as a potential surrogate for the invasive procedures. Results Ninety-nine patients with thyroid nodules (79 females and 20 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…Combining ACR TI-RADS and CFI vascularity score effectively improved the ability to differentiate malignant from benign TNs. This result is consistent with a previous study introduced by Baz et al [15]. It is also compatible with a similar study introduced by Appetecchia et al who reported that the combination of ultrasound imaging criteria and CFI vascularity increased the screening sensitivity and accuracy in distinguishing malignant TNs [19].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Combining ACR TI-RADS and CFI vascularity score effectively improved the ability to differentiate malignant from benign TNs. This result is consistent with a previous study introduced by Baz et al [15]. It is also compatible with a similar study introduced by Appetecchia et al who reported that the combination of ultrasound imaging criteria and CFI vascularity increased the screening sensitivity and accuracy in distinguishing malignant TNs [19].…”
Section: Discussionsupporting
confidence: 93%
“…The ROC curve found that, the sensitivity of CFI vascularity score alone is higher than the sensitivity of TI-RADS alone (85.19% vs 57.41%). A previous study introduced by Baz et al reported that CFI vascularity score alone has a 54.5% sensitivity and 100% speci city, 100% PPV, and 81.4% NPV for malignancy in TNs [15], which revealed less sensitivity but higher speci city for CFI vascularity score than those in our study.…”
Section: Discussioncontrasting
confidence: 69%
“…Aside from vascularity, and size, shear wave elastography (SWE) has been introduced into the evaluation of thyroid nodules in recent years [ 25 ]. Although these techniques are still not integrated into the present guidelines, their supplementation to various guidelines seems to improve the diagnosis of malignant nodules both in our study and in the available literature [ 26 ]. Further research is thus recommended on the supplementation of these techniques in nodules with nearly normal US characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to training and standardization, continuous monitoring of reliability statistics and formal feedback mechanisms have improved inter‐rater reliability estimates in observational studies 65 . Additionally, revision of modern risk criteria via the proposed inclusion of strain elastography or color doppler may improve objectivity and reduce variability between radiologists 66,67 . Up to 46% of thyroid ultrasounds are ordered unnecessarily and not in agreement with Choosing Wisely recommendations 68 .…”
Section: Discussionmentioning
confidence: 99%
“…65 Additionally, revision of modern risk criteria via the proposed inclusion of strain elastography or color doppler may improve objectivity and reduce variability between radiologists. 66,67 Up to 46% of thyroid ultrasounds are ordered unnecessarily and not in agreement with Choosing Wisely recommendations. 68 Hence, an improvement in inter-rater reliability is imperative in facilitating clinical uptake of thyroid ultrasound criteria since a lack of trust in reporting will lead to needlessly repeated ultrasounds, increased hospital expenditures, and unnecessary thyroid investigations.…”
Section: Discussionmentioning
confidence: 99%